S'gor Govt playing politics over water pact, say analysts - Daily Express, (KK) (Daily Express, 2015)
KUALA LUMPUR: The cancellation of water restructuring agreement between Selangor state government and the federal government seems to be dictated by political interests rather than to fulfill the need of the people.